Isolation, identification, and potential applications of endophytic bacteria from brown macroalga Hormophysa triquetra - Shazia Bibi (16500318) (2025)
The study aimed at isolation of bacterial endophytes from brown macroalga Hormophysa triquetra (HT). A total of 16 endophytic strains were obtained, belonging to five genera: Bacillus, Pseudomonas, Rothia, Lysinibacillus, and Stenotrophomonas. The isolates were identified based on 16S rRNA gene sequencing. Multiple assays — including hydrogen cyanide (HCN) production, phosphate solubilization, 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity, indole acetic acid (IAA) production, and protease enzyme activity were conducted. Moreover, salt tolerance assays and biocontrol tests against Fusarium oxysporum and Botrytis cinerea were also achieved. The results revealed promising plant growth–promoting and stress-mitigating capabilities among the isolated endophytes with strong performance by Bacillus cereus (HT3), which also proved to be effective against fungal strains and showed tolerance to saline conditions. Greenhouse experiments using HT3-treated tomato seedlings further confirmed the in vitro findings. Under abiotic (salinity) and biotic (F. oxysporum) stressed conditions, tomato seedlings treated with HT3 exhibited healthy growth regardless of stressors’ presence. This study highlights the potential of endophytes as biofertilizers and biocontrol agents, offering a promising step toward more sustainable and resilient agricultural practices. Other Information Published in: Biocatalysis and Agricultural Biotechnology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bcab.2025.103901